Calculation of Cost Budget Plan and Development of Implementation Method on Preservation of Aceh Selatan/Subulussalam Boundary Road - Sumut Province Boundaries - Husnita; Jufriza; M. Faisal; Iqbal; Jufandi; Herman Fithra; Maizuar (LPPM Universitas Malikussaleh, 2022)
Cost Budget Plan is a calculation of the amount of money needed for materials, tools and wages, as well as other costs related to project implementation. Goals to be achieved to recalculate the budget Road Reconstruction Workand the method of implementation in which there are work methods for tools, K3, quality control, and the S curve regarding cost, quality and the right time. The results obtained from the calculation, Preservation Reconstruction of the South Aceh Boundary Road / Subulussalam -Boundaries of North Sumatra Province The total budget cost is Rp. 3.412.934.913.00 As well as scheduling the implementation time using the S curve. The preparation of the Implementation method applied to the Project includes Ordinary Excavation, Asphalt Pavement Excavation without Cold Milling Machine, Grain Pavement Excavation, Selected Piles from excavation sources, Road Body Preparation, Grade Aggregate Foundation Layer A, Class B Aggregate Base Layer, Binder Impregnating Layer - Liquid/Emulsion Asphalt, Binder Impregnating Layer - Liquid/Emulsion Asphalt, Laston Wear Layer (AC-WC), Laston Intermediate Layer (AC-BC), Laston Foundation Layer (AC- base), Anti-flaking agent, Thermoplastic Road Marking, Hot Mix Asphalt Improvement, and Plant Control. in an effective way based on the plans.